2015
DOI: 10.3390/polym7091488
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Vancomycin-Loaded N-trimethyl Chitosan Nanoparticles

Abstract: Chronic intracellular infections caused by drug-resistant pathogens pose a challenge to the treatment of chronic osteomyelitis. Such treatment requires an intracellular delivery system for the sustained release of antibiotics such as vancomycin (VCM), which is an antibiotic of last resort used against many clinically resistant bacteria. In this work, we report VCM-loaded N-trimethyl chitosan (TMC) nanoparticles and their potential application for drug delivery. The results showed that the prepared nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(38 citation statements)
references
References 26 publications
1
36
0
1
Order By: Relevance
“…In our previous study, 17 the geometric mean diameter of VCM/TMC NPs obtained from atomic force microscopy was 200-325 nm, mean size distribution was 220-230 nm with a fairly monodisperse polydispersity index, which was almost ,0.2; meanwhile, VCM/TMC NPs carried a positive zeta potential of 14.6±0.8 mV at physiological pH, suggesting that these NPs are probably ionically stabilized against particle agglomeration due to the positive charges on their surface. In this study, the SEM results illustrated the presence of spherical VCM/TMC NPs with a smooth surface and compact structure.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In our previous study, 17 the geometric mean diameter of VCM/TMC NPs obtained from atomic force microscopy was 200-325 nm, mean size distribution was 220-230 nm with a fairly monodisperse polydispersity index, which was almost ,0.2; meanwhile, VCM/TMC NPs carried a positive zeta potential of 14.6±0.8 mV at physiological pH, suggesting that these NPs are probably ionically stabilized against particle agglomeration due to the positive charges on their surface. In this study, the SEM results illustrated the presence of spherical VCM/TMC NPs with a smooth surface and compact structure.…”
Section: Discussionmentioning
confidence: 84%
“…17 VCM/TMC NP-PTMC was prepared according to the reported literature with a slight improvement. 22 In short, PTMC solution was prepared in a glass dish sealed by a cover by dissolving approximately 0.67 g of polymer in 25 mL THF while stirring at room temperature until complete dissolution.…”
Section: Vcm Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Vancomycin is a glycopeptide antibiotic produced by Streptococcus Orientalis , well known for drug delivery applications, with a broad‐spectrum activity, including against methicillin‐resistant strains of Staphylococcus aureus . Vancomycin has often been encapsulated in spherical micro/nanoparticles made of polymeric materials such as poly(ϵ‐caprolactone), for bone implants, spray dried chitosan, or N‐trimethyl chitosan, prepared by single ionic complexation . Vancomycin‐containing coatings produced by electrodeposition and adsorption methods are also reported.…”
Section: Introductionmentioning
confidence: 99%
“…89 Similar sized vancomycin-loaded particles have been reported to demonstrate an efficient uptake by osteoblasts, resulting in their differentiation and elimination of the Staphylococcus aureus infection by controlled drug release. 90 It has also been suggested that the smaller NPs are easily engulfed by the APCs in comparison with the large sized ones and could potentially be used as drug delivery agent against tumors. 91 TMC NPs in the range 200-300 nm have also been reported to have more uptake as they are able to cross the nasal epithelial membrane owing to its small size.…”
Section: Particulate Effectmentioning
confidence: 99%